Mothers' perceptions about the nutritional status of their overweight children: a systematic review - Caliandra Francescatto; Natalia S. Santos; Vanessa F. Coutinho; Roberto F. Costa (Brazilian Society of Pediatrics, 2014)
Objective: this systematic review aims to explore and describe the studies that have as a primary outcome the identification of mothers' perception of the nutritional status of their children. Sources: the PubMed, Embase, LILACS, and SciELO databases were researched, regardless of language or publication date. The terms used for the search, with its variants, were: Nutritional Status, Perception, Mother, Maternal, Parents, Parental. Summary of the findings: after screening of 167 articles, 41 were selected for full text reading, of which 17 were included in the review and involved the evaluation of the perception of mothers on the nutritional status of 57,700 children and adolescents. The methodological quality of the studies ranged from low to excellent. The proportion of mothers who inadequately perceived the nutritional status of their children was high, and was the most common underestimation for children with overweight or obesity. Conclusion: despite the increasing prevalence of obesity in pediatric age, mothers have difficulty in properly perceiving the nutritional status of their children, which may compromise referral to treatment programs.